Alleviation of Methamphetamine Sensitization by Partially Lesioning Dopaminergic Terminals with 6-Hydroxydopamine in Nucleus Accumbens. (2nd November 2021) - Chen, Shu-Chun; Chen, Hsi; Yu, Seong-Jin; Chen, Yun-Hsiang; Wang, Yun
Amphetamine-type stimulants have become important and popular abused drugs worldwide. Methamphetamine (Meth) sensitization, characterized by a progressive increase in behavioral responses after repeated administration, has been reported in rodents and patients. This behavioral effect has been used as a laboratory model to study drug addiction and schizophrenia. The mesolimbic dopaminergic pathway plays a significant role in the development of Meth behavioral sensitization. Previous studies have reported that the ablation of nucleus accumbens (NAc) by electrolytic or thermal lesioning attenuates addictive behavior to opioids in animals. However, these studies were only conducted in opioid addictive rodents. Furthermore, these ablation procedures also damaged the non-dopaminergic neurons and fibers passing through the NAc. The purpose of this study was to examine the therapeutic effect of NAc lesioning by a selective dopaminergic toxin in Meth-sensitized animals. Adult mice received repeated administration of Meth for 7 days. Open-field locomotor activity and stereotype behavior were significantly increased after Meth treatment, suggesting behavior sensitization. A partial lesion of dopaminergic terminals was made through stereotaxic administration of dopaminergic toxin 6-hydroxydopamine (6-OHDA) to the NAc in the Meth -sensitized mice. Meth behavioral sensitization was significantly antagonized after the lesioning. Brain tissue was collected for qRT-PCR analysis. Repeated administration of Meth increased the expression of tyrosine hydroxylase (TH), BDNF, and Shati, a marker for Meth sensitization, in the NAc. Treatment with 6-OHDA significantly antagonized the upregulation of TH and Shati. Taken together, these data suggest that local administration of 6-OHDA mitigated Meth sensitization in chronic Meth-treated animals. Our data support a new surgical treatment strategy for Meth abuse.